Ulnar variance related to biological and training characteristics and handgrip strength in Portuguese skeletally immature female gymnasts - Amaral, L.; Claessens, A. L.; Ferreirinha, J. E.; Santos, P. J. (The Journal of Sports Medicine and Physical Fitness, 2012)
AIM: The aims of this study were to investigate the ulnar variance in a group of skeletally immature female gymnasts of different age and skill level and to investigate the left-right differences in ulnar variance and its relationship with biological and training characteristics and handgrip strength. METHODS: Thirty-three Portuguese skeletally immature female gymnasts (mean age 11.1 years) of different age-related categories completed a questionnaire detailing their training characteristics. Besides maturation, stature, body mass, and body composition, also handgrip strength of both hands were measured. Left and right ulnar variance was obtained using Hafner`s procedure and skeletal age through the Tanner-Whitehouse 3-method. RESULTS: Mean skeletal age (10.1±1.9 yr) is one year younger than chronological age (11.1±2.1 yr) and this discrepancy becomes more pronounced with increasing age-category. Gymnasts presented on average 6.1 years of training and 16.7 hours/week. A negative mean value for both the left and right ulnar variance measures was observed (between -1.7 mm and -3.1 mm) but with increasing age-category there is a trend that ulnar variance becomes more positive (between +0.3 mm and -1 mm). Significant differences between right and left ulnar variance were demonstrated. Correlations between ulnar variance and biological and training characteristics and handgrip strength are rather low and not significant, except for skeletal age (r=0.38), stature (r=0.41) and fat-free mass (r=0.48). CONCLUSION: Despite some significant results the main results of this study do not directly support the thesis that gymnastics training or handgrip strength are associated with ulnar variance.